Acceptable pregnancy rate of unstimulated intrauterine insemination: a retrospective analysis of 17, 830 cycles. (21st August 2014) - Honda, Tetsuro; Tsutsumi, Mai; Komoda, Fumio; Tatsumi, Kenichi
Abstract: Purpose: To evaluate the pregnancy rate (PR) of unstimulated intrauterine insemination (IUI). Methods: This was a retrospective study in a private fertility clinic. Between 2004 and 2013, a total of 4, 045 women underwent 17, 830 cycles of unstimulated IUI. The etiologies of subfertility in the couples were unexplained (51 %), male factor (36 %), coital problems (9.5 %), and cervical factor (3.5 %). Results: The PRs/cycle, between the 1st and 9th trials, in women <35, 35–37, 38–40, 41–42, and >42 years of age were 8.2, 7.3, 5.5, 3.6, and 0.9 %, respectively. In 10, 076 cycles in which the male partner had a total motile sperm count ≥5 million, the PRs in the respective age groups were 9.9, 8.6, 6.1, 4.8, and 1.2 %. The largest‐sized reported PRs for clomiphene citrate (CC)/IUI in the respective age groups were 11.5, 9.2, 7.3 4.3, and 1.0 % (4, 199 cycles in total, Dovey et al., FertilSteril, 2008;90:2281–2286). There were no significant differences in PRs between unstimulated IUI and CC/IUI. Conclusion: PR for unstimulated IUI was similar to the reported PR for CC/IUI. Although this was a retrospective study without a control group, to reduce multiple pregnancy rate, we believe that unstimulated IUI is a reasonable treatment.